Erosive lichen planus affecting the vulva: defining the disease, developing outcome measures and designing a randomised controlled trial - Simpson, Rosalind C. (2015)
Erosive lichen planus affecting the vulvovaginal region (ELPV) is a rare chronic inflammatory condition causing painful raw areas that can lead to scarring, at the vaginal entrance. Symptoms considerably impact upon daily function and quality of life. There is risk of cancerous change in affected skin of 1-3%.